2017
DOI: 10.17509/ijal.v6i2.4847
|View full text |Cite
|
Sign up to set email alerts
|

Learner Autonomy in the Indonesian Efl Settings

Abstract: Learner autonomy in Indonesian educational institutions has not commonly been listed as a teachinglearning objective, and most teachers seem to be hardly acquainted with learner autonomy (LA). Therefore, it is very essential to conduct a study of LA as perceived and experienced by school teachers and to find out the importance of LA training for professional development. A questionnaire was used to collect the data about English teachers' perceptions regarding LA and LA-based practices. In addition, an LA trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
114
1
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(129 citation statements)
references
References 6 publications
10
114
1
4
Order By: Relevance
“…Thus, tasks in the book are designed to follow this approach. Lengkanawati (2017) mentions that the implementation of curriculum 2013 gives new expectations in the learning process since the curriculum expects that there should be a change in the teaching and learning process, from transferring knowledge or giving information by the teacher to the students to allowing students to find information by themselves. Suherdi (2013) also states that the objective of curriculum 2013 will be achieved by paying attention to the educational content, switching the learning paradigm from the teacher centered approach into student-centered approach.…”
Section: Methodology Categorymentioning
confidence: 99%
“…Thus, tasks in the book are designed to follow this approach. Lengkanawati (2017) mentions that the implementation of curriculum 2013 gives new expectations in the learning process since the curriculum expects that there should be a change in the teaching and learning process, from transferring knowledge or giving information by the teacher to the students to allowing students to find information by themselves. Suherdi (2013) also states that the objective of curriculum 2013 will be achieved by paying attention to the educational content, switching the learning paradigm from the teacher centered approach into student-centered approach.…”
Section: Methodology Categorymentioning
confidence: 99%
“…In general, self-regulation refers to the process through which learners systematically direct their thoughts, feelings, and actions toward the attainment of their goals (Rajabi, 2012) [14]. In addition, Lengkanawati (2017) [10] believes that if we teach learners learn how to learn by the use of learning strategies, it is inevitable that we make them become autonomous which in turn will help them have better learning outcomes. As a result, SRL allows learners to learn to control their own behaviour through the social context in which learning occurred and interaction with selfreward.…”
Section: The Concept Of Learner Autonomy and Zimmerman's Model Of Selmentioning
confidence: 99%
“…However, most of teachers experience several common difficulties in lesson planning such as the way of formulating indicators, selecting materials, determining learning activities, selecting media and developing assessment procedure (Farid, 2014) [9]. Additionally, based on a study conducted in a Learner Autonomy-based teaching training, it was revealed that most teachers actually desired to integrate Learner Autonomy principles in their teachinglearning contexts, but the principles seem to be not feasible for the implementation (Lengkanawati, 2017) [10]. In line with the phenomenon, Farid (2014) [9] also mentions in his case study that the teacher made lesson plans tend to be not specific in depicting autonomy into the learning procedure.…”
Section: Introductionmentioning
confidence: 99%
“…Reference [10] Self-directed is a concept widely used in the context of learner autonomy and resumed as an entity. Reference [8] stated that the concept of autonomy, which is frequently associated with the concept of independent learning, self-directed and selfregulated learning has been viewed as a fundamental component of good teaching and learning. Additionally, based on Holec, he described autonomous learning as Reference [14]; 1) the ability to take charge of one's learning.…”
Section: B Autonomous Learningmentioning
confidence: 99%